Gerenciamento dos resíduos de serviços de saúde do pronto socorro de um hospital escola na cidade de Botucatu - Matarazzo, Drielly Daiane [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Health Care Waste (HCW) represents 1%, and it has presently gained a lot of importance. Adequate management is one of the great challenges to be faced by health care centers. It has gained distinction and been widely discussed by members of the sectors involved with sanitation, public health and environmental issues due to waste physical, chemical biological characteristics, which pose potential risk to the environment and public health. The present study aims at evaluating HCW internal management by following all its phases, determining indicators, classifying and quantifying, establishing production rates (kg /patient/day) for the sector and designing materials to disseminate appropriate HCW disposal in the Emergency Room of the UNESP University Hospital in the city of Botucatu according to the guidelines presently in force. : From June to October 2011, the waste flow was observed from its production to final disposal. Four weight measurements were performed on four consecutive days in the month of August by using a properly calibrated (in grams) digital scale at the times scheduled for collection of the produced waste. Hence, the daily and monthly amounts were estimated according to their classification. All the waste packaged in the bags in garbage cans in the Emergency Room for a 24-hour period was considered to be a sample. Separation was not adequately performed in that sector, and waste from Group A was mixed with that from Group D. The amount of infectious waste produced in the sector corresponded to 87.80 %, common waste to 10.93 % and recyclable waste to 1.27%. The mean daily HCW production was of 123.300 kg/day, and the total monthly production was of 3,822 kg/month, which was distributed as follows: Group A 3,355,750 kg/month; Group D 417,570 kg/month and recyclables 48,670 kg/month. The production rate corresponded to 0.47 kg/patient/day, thus showing... (Complete abstract click electronic access below)

Os Resíduos de Serviço de Saúde (RSS) representam 1% do total de resíduos produzidos, e vêm assumindo grande importância na atualidade e o gerenciamento adequado constitui-se num dos grandes desafios a ser enfrentado pelos centros de saúde, e está ganhando destaque e sendo discutido amplamente por membros de setores envolvidos com saneamento, saúde pública e questões ambientais devido às suas características físicas, químicas e biológicas que oferecem potencial de risco ao meio ambiente e à saúde pública. O presente estudo tem como objetivo avaliar o gerenciamento interno, acompanhar todas as etapas do manejo dos RSS, determinar os indicadores, caracterizar, classificar e quantificar, estabelecer a taxa de geração (kg /atendimento/dia) para o setor, e elaborar material para divulgação do descarte correto dos RSS da unidade do Pronto Socorro do HC - UNESP da cidade de Botucatu de acordo com as normas vigentes. Durante o período de junho a agosto de 2011, foi realizado o acompanhamento do fluxo de resíduos desde a sua geração até a disposição final. Foram realizadas quatro pesagens, durante quatro dias não consecutivos no mês de agosto, utilizando balança digital devidamente calibrada (em gramas), nos horários determinados para o recolhimento dos resíduos produzidos, estimando um valor diário e mensal, de acordo com sua classificação. Foram considerados como amostra todos os resíduos acondicionados nos sacos das lixeiras existentes no Pronto Socorro em um período de 24 horas. A segregação não foi realizada de forma adequada no setor, ocorrendo mistura dos resíduos do Grupo A com o Grupo D. A quantidade de resíduos infectantes produzidos no setor corresponde a 87.80 %, resíduos comuns 10.93 % e 1.27 % de recicláveis. .A produção média diária de RSS foi de 123.300 kg/dia e o total gerado no mês foi de 3.822 kg/mês assim distribuídos: Grupo... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Hospitais – Eliminação de resíduos; Saúde – Administração